Synthesis and determination of the absolute configuration of (−)-(5R,6Z)-dendrolasin-5-acetate from the nudibranch Hypselodoris jacksoni - Mudianta, I. Wayan; Challinor, Victoria L.; Winters, Anne E.; Cheney, Karen L.; De Voss, James J.; Garson, Mary J. (Beilstein Journal of Organic Chemistry, 2013)
A small sample of (−)-(5R,6Z)-dendrolasin-5-acetate, which was fully characterized by 2D NMR studies, was isolated from the nudibranch Hypselodoris jacksoni, along with the sesquiterpenes (+)-agassizin, (−)-furodysinin, (−)-euryfuran, (−)-dehydroherbadysidolide and (+)-pallescensone. A synthetic sample ([α]D −8.7) of the new metabolite was prepared by [1,2]-Wittig rearrangement of a geranylfuryl ether followed by acetylation of purified alcohol isomers. The absolute configuration at C-5 was established as R by the analysis of MPA ester derivatives of (Z)-5-hydroxydendrolasin obtained by preparative enantioselective HPLC.
Keywords: enantioselective HPLC; E/Z-isomers; Hypselodoris; natural products; nudibranch; sesquiterpene